2014
DOI: 10.1074/jbc.m114.570564
|View full text |Cite
|
Sign up to set email alerts
|

Taste of a Pill

Abstract: Background: Drug excretion into saliva has important clinical implications, but the mechanisms underlying salivary gland drug transport remain unclear. Results: OCT3 is highly expressed in secretory epithelial cells and mediates active metformin transport in salivary glands. Conclusion: OCT3 provides a unique pathway for metformin secretion and accumulation in salivary glands. Significance: Carrier-mediated salivary secretion can provoke drug-induced taste disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 29 publications
2
32
1
Order By: Relevance
“…For instance, it is expressed on the basolateral membrane of hepatocytes and placental epithelium [29,41], but in the lung, it is localized to the luminal membrane of bronchial epithelial cells [42]. In salivary glands, the OCT3 protein is localized at both basolateral and apical membranes of the secretory epithelial cells [43]. …”
Section: Molecular and Functional Characteristics Of Polyspecific mentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, it is expressed on the basolateral membrane of hepatocytes and placental epithelium [29,41], but in the lung, it is localized to the luminal membrane of bronchial epithelial cells [42]. In salivary glands, the OCT3 protein is localized at both basolateral and apical membranes of the secretory epithelial cells [43]. …”
Section: Molecular and Functional Characteristics Of Polyspecific mentioning
confidence: 99%
“…Carrier-mediated transport across cell membranes is particularly important for metformin because it is a hydrophilic (LogP=-1.43) drug with very low passive permeability [60]. In vitro and preclinical in vivo studies have demonstrated metformin is a substrate of hepatic OCT1 as well as OCT2, OCT3, MATEs and PMAT [19,43,62,70,72]. Metformin ameliorates hyperglycemia by decreasing hepatic glucose production, reducing gastrointestinal glucose absorption, and improving peripheral sensitivity to insulin [63].…”
Section: Impact Of Octs and Mates On Intracellular Levels Pharmacmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio of AUC values shown in Table 3 was calculated as AUC fib / AUC sus = AUC 0-t, fibers / AUC 0-t, suspension . The standard error of the mean (SEM) for PK parameters t 1/2z , AUC 0-72h , and AUC 0-∞ were generated using the bootstrap method with modification [39]. Briefly, using the R program, one of the measured ETR concentrations was randomly imputed at each time point to create 10,000 randomly-generated concentration-time profiles.…”
Section: Methodsmentioning
confidence: 99%